Hijacking the Supplies: Metabolism as a Novel Facet of Virus-Host Interaction - Mayer, Katharina A.; Stöckl, Johannes; Zlabinger, Gerhard J.; Gualdoni, Guido A. (Frontiers in Immunology, 2019)
Viral replication is a process that involves an extremely high turnover of cellular molecules. Since viruses depend on the host cell to obtain the macromolecules needed for their proper replication, they have evolved numerous strategies to shape cellular metabolism and the biosynthesis machinery of the host according to their specific needs. Technologies for the rigorous analysis of metabolic alterations in cells have recently become widely available and have greatly expanded our knowledge of these crucial host–pathogen interactions. We have learned that most viruses enhance specific anabolic pathways and are highly dependent on these alterations. Since uninfected cells are far more plastic in their metabolism, targeting of the virus-induced metabolic alterations is a promising strategy for specific antiviral therapy and has gained great interest recently. In this review, we summarize the current advances in our understanding of metabolic adaptations during viral infections, with a particular focus on the utilization of this information for therapeutic application.